2001
DOI: 10.1073/pnas.181228598
|View full text |Cite
|
Sign up to set email alerts
|

A cell-based system that recapitulates the dynamic light-dependent regulation of the vertebrate clock

Abstract: The primary hallmark of circadian clocks is their ability to entrain to environmental stimuli. The dominant, and therefore most physiologically important, entraining stimulus comes from environmental light cycles. Here we describe the establishment and characterization of a new cell line, designated Z3, which derives from zebrafish embryos and contains an independent, light-entrainable circadian oscillator. Using this system, we show distinct and differential light-dependent gene activation for several central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
143
2
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(166 citation statements)
references
References 37 publications
15
143
2
6
Order By: Relevance
“…2a,c). The expression of cry1a and per2 is strongly induced in surface fish, similar to previous reports in zebrafish 22,[34][35][36] . This acute light response is greatly reduced, though still statistically significant, in Pachón cavefish and does not occur in Chica cavefish.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…2a,c). The expression of cry1a and per2 is strongly induced in surface fish, similar to previous reports in zebrafish 22,[34][35][36] . This acute light response is greatly reduced, though still statistically significant, in Pachón cavefish and does not occur in Chica cavefish.…”
Section: Resultssupporting
confidence: 90%
“…In this study, we have explored, under both laboratory and field conditions, how the circadian clock has evolved in this species. In the laboratory, surface fish show a robust circadian oscillation in per1 gene expression, as has been previously reported for zebrafish and other teleost species 20,31,32,34,42 . A high-amplitude per1 rhythm is also apparent in surface fish under natural conditions.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, cultured lines of embryonal zebrafish cells, which recapitulate most features of the zebrafish clock system, have been established as an attractive vertebrate cell-based model suitable for the examination of the light signaling pathway and its impact on the circadian clock. 56) Studies using these cell lines have revealed critical roles for redox control and MAPK signaling pathways in light-dependent circadian entrainment 57) (Fig. 2).…”
Section: Zebrafish As a Model System For Circadian Clock Studymentioning
confidence: 99%
“…The immunoprecipitated materials and whole cell extracts were analyzed by immunoblotting with anti-VP16 (zCRY1a and chimera 17), anti-zCRY3 (chimeras 11, 18, and zCRY3), anti-V5 (zB-MAL3), or anti-FLAG antibodies (zCLOCK1). The abbreviations c 5,11,12,13,14,16,17, and 18 respectively indicate chimeras 5, 11, 12, 13, 14, 16, 17, and 18. localization (Fig. 4C, lanes 7-18).…”
Section: Fig 2 Determination Of the Zcry1a Regions Required For Tramentioning
confidence: 99%